The effect of sustainability practices on financial leakage in the hotel industry in Jordan. (June 2016) - Alzboun, Nidal; Khawaldah, Hamzah; Backman, Kenneth; Moore, DeWayne
Abstract: This study aims to assess the effect of sustainability practices on financial leakages in the hotel industry in Jordan. A self-administered survey was distributed to hotel managers in all 213 classified hotels in Amman, Aqaba, Petra, and the Dead Sea area. Of these, 163 questionnaires were returned with a response rate of 76.5%. Confirmatory Factor Analysis and Structural Equation Modeling were used to test research hypotheses. Despite that many studies have predicted sustainability practices to have a negative effect on financial leakages, the results of this study indicated that sustainability practices didn't reduce the financial leakage level in Jordanian hotels. However, financial leakages are predicted to be reduced through sustainability practices over time. These results could help hotels to develop financial and conservation strategies benefiting their local economies, resources, and cultures. Future research may extend this work to other tourism businesses.